A novel method for preparing nanoparticle titanium catalyst and its application in polyester synthesis

Through the preparation method of the new nanoparticle titanium catalyst, the problem of inadequate crystallization behavior in polyester synthesis is solved, efficient catalysis and crystallization promotion of polyester are achieved, and the industrial application of titanium catalysts is promoted.

CN119775542APending Publication Date: 2025-04-08ZHEJIANG TONGKUN NEW MATERIALS RES INST CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411693326.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

In the synthesis of existing titanium catalysts, there are problems in the fact that the crystallization behavior of the current process is not suitable for the current process and affects the condensed state structure and mechanical properties of the polyester products.

Method used

Using a new nanoparticle type titanium catalyst preparation method, nanoparticles are formed by covalently bonding the organic ligand under ammonia water catalysis, and complex coordination reaction occurs with the titanium source to form a polyester ester exchange catalyst supported by titanium. This catalyst can not only catalyze the ester exchange reaction during polymerization, but also promote polyester crystallization after polymerization.

Benefits of technology

It significantly improves the crystallization behavior and nucleation and crystallization capabilities of titanium-based polyester, so that it can basically adapt to the current spinning and elastic adding processes, reduces promotion resistance, and promotes the industrial application of titanium-based catalysts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005151533350000151
    Figure BDA0005151533350000151
Patent Text Reader

Abstract

The invention discloses a novel method for preparing a nanoparticle-type titanium catalyst. After hydrolyzing silicate and before condensing to form nanoparticles, the ligand of the catalyst is covalently bonded to the side chain of silanol, and then ammonia water is added to catalyze the mutual condensation between silanols to obtain nanoparticles with smaller particle sizes. After adding a titanium source, the catalyst is quickly complexed and coordinated with the titanium atom of the catalytic center to fix the catalytic center on the nanoparticles to obtain a nanoparticle-type catalyst. The catalyst can act as a catalyst during polymerization to catalyze the transesterification reaction to generate polyester; after polymerization, the catalyst can act as a nucleating crystallizing agent to promote the crystallization of polyester, killing two birds with one stone. The catalyst has good catalytic performance and significantly improves the nucleating crystallization performance of polyester, achieving the expected goal. The synthetic method adopted is convenient to operate, simple and feasible, and the prepared product has the advantages of being green and environmentally friendly, low in price, etc. It is feasible in actual operation, which is conducive to promoting the industrial application and promotion of titanium catalysts in the textile industry.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polyester synthesis, and in particular to a method for preparing a novel nano-particle titanium catalyst and its application in polyester synthesis. Background Art

[0002] The polyester industry currently has an annual production capacity of more than 60 million tons, and its finished products include fiber filaments, films, packaging boxes, etc., which penetrate into all aspects of production and life. Polyester, especially its main variety polyethylene terephthalate (PET), usually uses heavy metal antimony catalysts when synthesizing it. Therefore, a certain amount of heavy metal antimony will be precipitated during its application, subsequent processing and landfill, polluting water bodies and the natural environment, causing a certain degree of harm to humans and animals.

[0003] Considering the economic feasibility and the performance of the final polyester product, it is generally believed that titanium catalysts are the most likely to replace heavy metal antimony catalysts. Although germanium catalysts have excellent performance, their large-scale application is limited due to their high prices. At present, there are still some technical bottlenecks in titanium catalysts. For example, although titanium polyester and antimony polyester can be basically consistent in terms of molecular weight, intrinsic viscosity and other indicators, the amount of titanium catalyst added is small, the system is highly clean, and unlike antimony catalysts, it will not be reduced to form antimony nanoparticles (nucleation crystallization promoter) during the polymerization process, resulting in a significant decrease in the crystallization rate and ability of polyester, thereby affecting the condensed structure and mechanical properties of polyester products.

[0004] From the perspective of PET fiber spinning and texturing, the crystallization behavior of polyester significantly affects the spinning process and texturing process. Only when the properties and crystallization behavior of titanium polyester are close to those of the current conventional antimony polyester, its large-scale industrial application is possible. Therefore, the development of titanium catalysts, in addition to improving the hue of polyester, also needs to change the crystallization behavior of titanium polyester to adapt it to the current melt direct spinning process and reduce the adjustment range of post-process parameters such as texturing.

[0005] Inspired by antimony-based catalysts, if we can develop a catalyst that can act as a catalyst during polymerization, catalyzing the ester exchange reaction to produce polyester; and after polymerization, it can also act as a nucleating crystallization agent to promote polyester crystallization, it will kill two birds with one stone. Summary of the invention

[0006] In order to solve one or some technical problems existing in the prior art, one of the purposes of this application is to provide a new method for preparing nanoparticle titanium catalyst. The synthesis method is convenient, simple and feasible, and the prepared product has the advantages of being green, environmentally friendly and low-priced.

[0007] The second purpose of the present application is to provide a new type of nanoparticle titanium catalyst for use in polyester synthesis. Since the nanoparticles have the ability to catalyze and promote crystallization, they can catalyze the ester exchange reaction after addition, and can also significantly increase the nucleation sites of polyester crystallization, improve the nucleation and crystallization ability of titanium-based polyester, and improve the crystallization behavior of titanium-based polyester, so as to ensure that titanium-based polyester can basically adapt to the current spinning, stretching and other processes, effectively reduce the resistance to promotion, and promote the industrial application of titanium-based catalysts.

[0008] In order to solve the above existing technical problems, one of the purposes of this application is achieved by adopting the following technical solution:

[0009] A novel method for preparing a nanoparticle titanium catalyst, characterized in that: the preparation method comprises

[0010] S1, dissolving conventional silicate chemicals and epoxy-containing silicate chemicals in a solvent, stirring until a uniform and stable solution is formed, to obtain solution A, wherein the solvent is at least one of ethylene glycol and diethylene glycol;

[0011] S2, adding an organic ligand compound to the solution A in step S1, so that the organic ligand in the organic ligand compound reacts with the silanol with a functional group in the solution A to achieve covalent bonding, thereby obtaining a solution B;

[0012] S3, gradually adding hydrochloric acid aqueous solution to the above solution B, stirring continuously and heating, then stirring the mixed solution evenly and reacting it at 50-210° C. for 1-48 hours, so that the silicate chemicals are hydrolyzed to obtain a short-term stable silanol solution C;

[0013] S4, adding ammonia water to the solution C in step S3 to catalyze the mutual condensation of semi-stable silanols to form nanoparticles, thereby forming a dispersion D;

[0014] S5, the dispersion D in step S4 contains water, water and ammonia are removed by heating, and then a titanium source is added, and the organic ligands on the surface of the nanoparticles react with the titanium source to form a complex coordination reaction to obtain a dispersion E, which is a mixture of a catalyst and an alcohol by-product;

[0015] S6, the dispersion E in step S5 is centrifuged and washed with deionized water to obtain a white slurry pre-product F;

[0016] S7, dispersing the pre-product F in deionized water, stirring and dispersing for 0.1 to 3 hours, performing high-speed shearing treatment for 0.1 to 3 hours using a high-speed disperser, and then grinding for 0.5 to 5 hours using a sand mill to obtain a finished catalyst product.

[0017] When the novel nanoparticle-type titanium catalyst is prepared by the above method, the organic ligand and the silanol compound are first chemically reacted to form a covalently linked compound, and then the silanol compounds are mutually condensed to form nanoparticles. Since the side chain of the silanol is covalently linked to the side chain of the organic ligand, its stabilizing effect ensures that the particle size of the formed particles is small, controllable and has a small distribution coefficient. The nanoparticles covalently bonded to the side chain of the organic ligand then react with a titanium source to obtain a polyester transesterification catalyst loaded with titanium. The nanoparticles with organic ligands can be regarded as a special ligand, and a titanium catalyst is obtained after chelating with titanium. From another perspective, it can also be considered that the catalytic active center titanium atom is loaded on the nanoparticles covalently bonded to the organic ligand, achieving the dual effects of catalyzing transesterification and promoting crystallization. Its existence is equivalent to a crystallization nucleating agent, which significantly improves and improves the crystallization ability of the polyester after polymerization. Moreover, the preparation method is convenient and feasible, can effectively catalyze the ester exchange condensation reaction and the nucleation crystallization ability of polyester, is green, environmentally friendly and pollution-free, has low cost, conforms to the current development trend of the industry, meets the current development needs of the industry, and can play a certain role in promoting the industrial application of titanium catalysts in the polyester and textile industries.

[0018] Preferably, the conventional silicate chemical in step S1 is at least one of tetramethyl orthosilicate, tetraethyl orthosilicate, tetrapropyl orthosilicate, tetrabutyl orthosilicate, tetrapentyl orthosilicate, tetra(2-ethylbutyl)silicate, tetra(isopropyl)silicate, tetra(2-methoxyethanol)silicate, tetra(2-ethylbutyl)silicate, tetra(2-ethylhexyl)silicate, tetraoctyl silicate, tetraphenyl silicate, and tetradecoxysilicon.

[0019] Preferably, the epoxy-containing silicate chemical in step S1 is at least one of 3-glycidyl propoxy trimethoxysilane, 3-glycidyl ether oxypropyl triethoxy silane, 3-glycidyl propoxy tripropoxy silane, and 3-glycidyl propoxy tributoxy silane.

[0020] Preferably, the molar ratio of the conventional silicate chemical to the epoxy-containing silicate chemical is 1-9:9-1, and the mass ratio of the total silicate chemical to the solvent A is 1-4:9-6.

[0021] Preferably, the molar ratio of the conventional silicate chemical to the epoxy-containing silicate chemical is 1-8:9-2.

[0022] In the process of preparing the novel nanoparticle-type titanium catalyst by the above method, silanol mainly comes from two silicon sources, one of which is a conventional silicon source, namely, at least one of tetramethyl orthosilicate, tetraethyl orthosilicate, tetrapropyl orthosilicate, tetrabutyl orthosilicate, tetrapentyl orthosilicate, tetra(2-ethylbutyl) silicate, tetra(isopropyl) silicate, tetra(2-methoxyethanol) silicate, tetra(2-ethylbutyl) silicate, tetra(2-ethylhexyl) silicate, tetraoctyl silicate, tetraphenyl silicate, and tetradecyloxysilicon. By controlling the amount of these two silicon sources, the amount of stable side chains can be effectively controlled, and the effective adjustment of the particle size of the nanoparticles can be achieved.

[0023] Preferably, the reaction temperature in step S2 is 100-200° C., and the reaction time is 1-5 h.

[0024] Preferably, the organic ligand compound in step S2 includes at least one of citric acid, oxalic acid, gluconic acid, and di-o-vanillin (diphenyl ether) phenylimine.

[0025] Preferably, in step S2, the molar ratio of the silanol with epoxy group to the organic ligand compound is 2-8:8-2.

[0026] Preferably, in step S2, the molar ratio of the silanol with epoxy group to the organic ligand compound is 3-8:7-2.

[0027] Preferably, the catalytic reaction temperature in step S4 is 30-200° C., the reaction time is 1-5 h, and the particle size of the formed nanoparticles is 5-300 nanometers.

[0028] Since the existing chain segments are relatively long (new chain segments generated after the glycidyl ether oxypropyl chain segments react with the organic ligand compounds), they play a stabilizing role and the formed particles are relatively small, with a particle size in the nanometer range and a particle size between 5 and 300 nanometers.

[0029] Preferably, the reaction temperature in step S5 is 100-200° C., the reaction time is 1-24 h, and the titanium source is at least one of tetraethyl titanate, tetrapropyl titanate, tetrabutyl titanate, tetraisopropyl titanate, tetra-tert-butyl titanate, and 2-ethyl-1-hexanol titanium.

[0030] Preferably, in step S5, the molar ratio of the silanol with epoxy group to the titanium source is 5-9:5-1.

[0031] Preferably, in step S5, the molar ratio of the silanol with epoxy group to the titanium source is 6-9:4-1.

[0032] Preferably, the catalyst particles in the finished catalyst product in step S7 have a particle size of 5 to 300 nm, the main component of the dispersion medium is deionized water, and the percentage of the effective substance Ti is 0.5% to 30%.

[0033] Preferably, the solid content of the finished catalyst product in step S7 is 2-15%, and the titanium content is 0.5% to 5%.

[0034] Preferably, the sand mill grinding time in step S7 is 0.5-4.5 h, the solid content of the finished catalyst is 2-14%, and the titanium content is 0.5% to 4.5%.

[0035] The second purpose of this application is achieved by the following technical solution:

[0036] A novel nanoparticle titanium catalyst is used in polyester synthesis, characterized in that: the application method comprises:

[0037] A1. Add the finished catalyst and dibasic acid to a diol solution at a temperature of 20 to 120° C. and stir rapidly until a uniform and stable mixed dispersion is formed. The amount of the finished catalyst added is based on the amount of titanium element, and the content of the effective substance Ti in the added finished catalyst in the polyester is 1 to 100 ppm;

[0038] A2, using diol and dibasic acid as raw materials to carry out esterification, pre-polycondensation and final polycondensation in sequence to prepare polyester in the form of chips, filaments or staple fibers, wherein the reaction temperature of the polyester is 220-280° C., the reaction pressure is 30 Pa-0.4 MPa, and the reaction time is 3.5-10.0 h;

[0039] A3. Add the mixed dispersion before esterification or polycondensation during the polyester synthesis.

[0040] Titanium atoms with catalytic activity are coordinated and complexed on nanoparticles, so the nanoparticles have catalytic ability and act as a catalyst for ester exchange during polyester synthesis. Due to the small particle size and large specific surface area, the catalytic activity is relatively high. After the catalysis is completed, the nanoparticles are evenly distributed in the polyester, acting as heterogeneous nucleating agents and promoters to promote the nucleation and crystallization of polyester, change the condensed structure of polyester, and improve the mechanical properties of polyester. Due to the small particle size, more nucleation sites are introduced per unit added mass, and the ability to promote crystallization nucleation is greater. Since nanoparticles have the ability to catalyze and promote crystallization at the same time, they can reflect the catalytic ability of ester exchange reaction after addition, and can also significantly increase the nucleation sites of polyester crystallization, improve the nucleation and crystallization ability of titanium polyester, and improve the crystallization behavior of titanium polyester, so as to ensure that titanium polyester can basically adapt to the current spinning, stretching and other processes, effectively reduce the resistance to promotion, and promote the industrial application of titanium catalysts.

[0041] Preferably, the polyester includes at least one of polyethylene terephthalate, polybutylene terephthalate and polybutylene adipate.

[0042] Preferably, the dibasic acid includes at least one of purified terephthalic acid, isophthalic acid, naphthalene dicarboxylic acid, succinic acid, adipic acid, biphenyl dicarboxylic acid, and cyclohexane dicarboxylic acid; the diol includes at least one of ethylene glycol, 1,3-propylene glycol, 1,4-butanediol, 1,5-pentanediol, and 1,4-cyclohexanedimethanol; and the molar ratio of the dibasic acid to the diol is 1:1.2 to 2.0.

[0043] Preferably, the esterification temperature of the raw materials of the diol and the dibasic acid in step A2 is 220-260°C, the esterification pressure is normal pressure-0.4 MPa, and the esterification time is 2.0-4.0 h; the pre-polycondensation temperature is 260-280°C, the vacuum degree is 100-150 Pa, and the reaction time is 1.0-3.5 h; the final polycondensation temperature is 270-290°C, the vacuum degree is 5-80 Pa, and the reaction time is 1.0-3.5 h.

[0044] Compared with the prior art, the present invention has the following beneficial effects:

[0045] 1. In view of the difference in crystallization behavior between titanium polyester and antimony polyester, the main characteristics of nanoparticle titanium catalyst are: silanol covalently bonded with organic ligands undergoes condensation reaction under the catalysis of ammonia water to form nanoparticles. At the same time, most of the organic ligand chain segments extend in the solvent, stabilizing the nanoparticles formed by condensation, making the particle size smaller and the distribution narrower. Since the catalytic center titanium atom is coordinated to the organic ligand of the nanoparticle, the synthesized nanoparticles have the ability to catalyze the ester exchange of polyester in the polycondensation stage. Since the catalyst itself is a nanoparticle structure, it has a small particle size and a large specific surface area, and has a higher catalytic activity. Since the relevant ligands have a good ability to stabilize titanium atoms, the catalyst is resistant to hydrolysis, and the polyester produced has a good hue.

[0046] 2. After the polymerization stage is completed, the catalyst nanoparticles still remain in the polyester system and are evenly dispersed in the polyester system. They then act as the nucleation center of the crystal to change the crystallization kinetics and the corresponding physical properties of the obtained polyester. The new nanoparticle catalyst prepared by this method integrates catalysis and nucleation functions. When used in the synthesis of titanium polyester, the titanium polyester and antimony polyester can have similar crystallization temperatures without negatively affecting the polymerization rate and the hue of the polyester. This enables titanium polyester to basically adapt to current spinning, texturing and other processes, providing convenience for subsequent applications, effectively reducing promotion resistance, reducing the promotion cost of titanium catalysts, and promoting the industrial application of titanium catalysts.

[0047] 3. After the silicate is hydrolyzed and before condensation to form nanoparticles, the ligand of the catalyst is covalently bonded to the side chain of the silanol, and then ammonia water is added to catalyze the mutual condensation between the silanols to obtain nanoparticles with smaller particle sizes. At the same time, the surface of the nanoparticles is rich in organic ligands, which quickly complex and coordinate with the titanium atom of the catalytic center after the addition of the titanium source to fix the catalytic center on the nanoparticles to obtain a nanoparticle-type catalyst, which can act as a catalyst during polymerization to catalyze the transesterification reaction to produce polyester; after polymerization, it can also act as a nucleating crystallizing agent to promote the crystallization of polyester, killing two birds with one stone, and the catalyst has good catalytic performance, and the improvement of the nucleation and crystallization performance of polyester is also relatively obvious, achieving the expected goal. The synthetic method adopted is convenient, simple and feasible, and the prepared product has the advantages of green environmental protection and low price. It is feasible in actual operation, and the effect of promoting polyester crystallization is obvious, which is conducive to promoting the industrial application and promotion of titanium catalysts in the textile industry. DETAILED DESCRIPTION

[0048] Below, the present application is further described in conjunction with specific implementation methods. It should be noted that, under the premise of no conflict, the various embodiments or technical features described below can be arbitrarily combined to form new embodiments.

[0049] Embodiment 1:

[0050] A method for preparing a novel nanoparticle titanium catalyst, wherein the solvent is diethylene glycol, the conventional silicate chemical is tetraethyl orthosilicate, the epoxy-containing silicate chemical is 3-glycidyloxypropyltriethoxysilane, the organic ligand compound is citric acid, and the titanium source is tetrabutyl tetratitanate. The preparation method comprises the following steps: (1) dissolving 12.5 g of tetraethyl orthosilicate and 5.57 g of 3-glycidyloxypropyltriethoxysilane in 90.34 g of diethylene glycol, stirring until a uniform and stable solution is formed, to obtain solution A; and (2) adding 3.84 g of the organic ligand compound citric acid to solution A, so that the organic ligand reacts with the silicate with a functional group to achieve covalent bonding, to obtain solution B. The reaction temperature is 150°C and the reaction time is 2h; (3) 10.80g of 5% hydrochloric acid aqueous solution is gradually added to the above solution B, and the mixture is stirred continuously. Then the mixed solution is stirred evenly and placed at 50°C for 2h to hydrolyze the silicate chemicals to obtain a short-term stable silanol solution C; (4) 16.20g of 10% ammonia water is added to solution C to catalyze the mutual condensation of semi-stable silanols to form nanoparticles, forming a dispersion D; (5) The water and ammonia in the dispersion D are removed by heating, and then 25.74g of tetrabutyl titanate is added. The organic ligands on the surface of the nanoparticles react with the titanium source to obtain a dispersion E, which is a mixture of the catalyst and alcohol by-products; (6) The dispersion E is centrifuged and washed 8 times with deionized water to obtain a white slurry pre-product F; (7) The pre-product F is dispersed in deionized water, stirred and dispersed for 1h, and then subjected to high-speed shear treatment for 0.5h using a high-speed disperser, and then ground with a sand mill for 3h to obtain a finished catalyst. The particle size of the catalyst particles is between 100-200 nm, the dispersion medium is water, the percentage of the effective substance (Ti) is 1%, and the amount of the catalyst added to the polyester synthesis is calculated as 5 ppm of the amount of polyester generated.

[0051] A novel nanoparticle titanium catalyst is used in polyester synthesis, wherein the diol is purified terephthalic acid and the dibasic acid is ethylene glycol. The application method includes:

[0052] 333.3g of purified terephthalic acid, 160g of ethylene glycol and the finished catalyst dispersion were added to the reactor. After nitrogen was replaced 3 times, nitrogen was filled to 0.15MPa for esterification reaction. After the esterification water reached the theoretical value, the pre-polycondensation and final polycondensation reactions were started; wherein, the esterification temperature was 230-240°C, the pressure was normal pressure-0.4MPa, and the esterification time was 2.5h; the pre-polycondensation temperature was 265°C, the vacuum degree was 100-150Pa, and the reaction time was 1.0h; the final polycondensation temperature was 272°C, the vacuum degree was 5-20Pa, and the reaction time was 1.5h, until the stirring power reached the set value, and the material was cut into pellets to make slices.

[0053] Example 2

[0054] Synthesis and dispersion process of a new type of nanoparticle titanium catalyst:

[0055] The solvent is diethylene glycol, the conventional silicate chemical is tetraethyl orthosilicate, the epoxy silicate chemical is 3-glycidyloxypropyltriethoxysilane, the organic ligand compound is citric acid, and the titanium source is tetrabutyl tetratitanate. The preparation method comprises the following steps:

[0056] (1) Dissolve 12.5g of tetraethyl orthosilicate and 11.14g of 3-glycidyloxypropyltriethoxysilane in 118.18g of diethylene glycol and stir until a uniform and stable solution is formed to obtain solution A; (2) Add 7.69g of citric acid, an organic ligand compound, to solution A to react the organic ligand with the silicate with functional groups to achieve covalent bonding to obtain solution B. The reaction temperature is 150°C and the reaction time is 2h; (3) Add 12.96g of 5% hydrochloric acid aqueous solution to the above solution B gradually and stir continuously, then stir the mixed solution evenly and place it at 50°C for 2h to react so that the silicate chemicals are hydrolyzed to obtain a short-term stable silanol solution C; (4) Add ammonia water to 19.44g of 10% solution C to catalyze the mutual condensation of semi-stable silanols to form nanoparticles to form a dispersion D; (5) Heat and remove water and ammonia in the dispersion D. Then, 51.47g of tetrabutyl titanate was added, and the organic ligand on the surface of the nanoparticles reacted with the titanium source to form a complex coordination reaction, thereby obtaining a dispersion E, which was a mixture of a catalyst and alcohol byproducts; (6) the dispersion E was centrifuged and washed 8 times with deionized water to obtain a white slurry pre-product F; (7) the pre-product F was dispersed in deionized water, stirred and dispersed for 1 hour, and then subjected to high-speed shear treatment for 0.5 hours using a high-speed disperser, and then ground with a sand mill for 3 hours to obtain a finished catalyst. The particle size of the catalyst particles was between 50-100nm, the dispersion medium was water, the percentage of the effective substance (Ti) was 1%, and the amount of the catalyst added to the polyester synthesis was calculated as 5ppm of the amount of polyester produced.

[0057] Polyester Synthesis:

[0058] Among them, the diol is taken as purified terephthalic acid, and the dibasic acid is taken as ethylene glycol. 333.3g of purified terephthalic acid, 160g of ethylene glycol and the finished dispersion of the catalyst are added into the reactor. After nitrogen is replaced 3 times, nitrogen is filled to 0.15MPa for esterification reaction. After the esterification water reaches the theoretical value, the above dispersion is added to start the pre-condensation and final polycondensation reactions; wherein, the esterification temperature is 230-240°C, the esterification pressure is normal pressure-0.4MPa, and the esterification time is 2.5h; the pre-condensation temperature is 265°C, the vacuum degree is 100-150Pa, and the reaction time is 1.0h; the final polycondensation temperature is 272°C, the vacuum degree is 5-20Pa, and the reaction time is 1.5h, until the stirring power reaches the set value, and the material is cut into slices.

[0059] Example 3

[0060] Synthesis and dispersion process of a new type of nanoparticle titanium catalyst:

[0061] The solvent is diethylene glycol, the conventional silicate chemical is tetraethyl orthosilicate, the epoxy silicate chemical is 3-glycidyloxypropyl triethoxysilane, the organic ligand compound is citric acid, and the titanium source is tetrabutyl tetratitanate. The preparation method comprises the following steps: (1) dissolving 12.5 g of tetraethyl orthosilicate and 16.71 g of 3-glycidyloxypropyl triethoxysilane in 146.02 g of diethylene glycol solvent, stirring to form a uniform and stable solution, and obtaining solution A; and (2) adding 11.63 g of citric acid, an organic ligand compound, to solution A, so that the organic ligand reacts with the silicate with functional groups to achieve covalent bonding, and obtaining solution B. The reaction temperature is 150°C and the reaction time is 2h; (3) 15.12g of 5% hydrochloric acid aqueous solution is gradually added to the above solution B, and the mixture is stirred continuously. Then the mixed solution is stirred evenly and placed at 50°C for 2h to hydrolyze the silicate chemicals to obtain a short-term stable silanol solution C; (4) Ammonia water is added to 22.68g of 10% solution C to catalyze the mutual condensation of semi-stable silanols to form nanoparticles to form a dispersion D; (5) The water and ammonia in the dispersion D are removed by heating. Then 77.21g of tetrabutyl titanate is added, and the organic ligands on the surface of the nanoparticles react with the titanium source to obtain a dispersion E, which is a mixture of the catalyst and alcohol by-products; (6) The dispersion E is centrifuged and washed 8 times with deionized water to obtain a white slurry pre-product F; (7) The pre-product F is dispersed in deionized water, stirred and dispersed for 1h, and then subjected to high-speed shear treatment for 0.5h using a high-speed disperser, and then ground by a sand mill for 3h to obtain a finished catalyst. The particle size of the catalyst particles is between 5-50 nm, the dispersion medium is water, the percentage of the effective substance (Ti) is 1%, and the amount of the catalyst added to the polyester synthesis is calculated as 5 ppm of the amount of polyester generated.

[0062] Polyester Synthesis:

[0063] Among them, the diol is taken as purified terephthalic acid, and the dibasic acid is taken as ethylene glycol. 333.3g of purified terephthalic acid, 160g of ethylene glycol and the finished catalyst dispersion are added into the reactor. After nitrogen is replaced 3 times, nitrogen is filled to 0.15MPa for esterification reaction. After the esterification water output reaches the theoretical value, the pre-condensation and final condensation reactions are started; wherein, the esterification temperature is 230-240°C, the esterification pressure is normal pressure-0.4MPa, and the esterification time is 2.5h; the pre-condensation temperature is 265°C, the vacuum degree is 100-150Pa, and the reaction time is 1.0h; the final condensation temperature is 272°C, the vacuum degree is 5-20Pa, and the reaction time is 1.0h, until the stirring power reaches the set value, and the material is cut into pellets to make slices.

[0064] Example 4

[0065] Synthesis and dispersion process of a new type of nanoparticle titanium catalyst:

[0066] The solvent is diethylene glycol, the conventional silicate chemical is tetraethyl orthosilicate, the epoxy silicate chemical is 3-glycidyloxypropyl triethoxysilane, the organic ligand compound is citric acid, and the titanium source is tetrabutyl tetratitanate. The preparation method comprises the following steps: (1) dissolving 12.5 g of tetraethyl orthosilicate and 11.14 g of 3-glycidyloxypropyl triethoxysilane in 118.18 g of diethylene glycol solvent, stirring until a uniform and stable solution is formed, to obtain solution A; and (2) adding 8.45 g of citric acid, an organic ligand compound, to solution A, so that the organic ligand reacts with the silanol with a functional group to achieve covalent bonding, to obtain solution B. The reaction temperature is 150°C and the reaction time is 2h; (3) 12.96g of 5% hydrochloric acid aqueous solution is gradually added to the above solution B, and the mixture is stirred continuously. Then the mixed solution is stirred evenly and placed at 50°C for 2h to hydrolyze the silicate chemicals to obtain a short-term stable silanol solution C; (4) Ammonia water is added to 19.44g of 10% solution C to catalyze the mutual condensation of semi-stable silanols to form nanoparticles to form a dispersion D; (5) The water and ammonia in the dispersion D are removed by heating. Then 56.62g of tetrabutyl titanate is added, and the organic ligands on the surface of the nanoparticles react with the titanium source to obtain a dispersion E, which is a mixture of the catalyst and alcohol by-products; (6) The dispersion E is centrifuged and washed 8 times with deionized water to obtain a white slurry pre-product F; (7) The pre-product F is dispersed in deionized water, stirred and dispersed for 1h, and then subjected to high-speed shear treatment for 0.5h using a high-speed disperser, and then ground by a sand mill for 3h to obtain a finished catalyst. The particle size of the catalyst particles is between 40-80 nm, the dispersion medium is water, the percentage of the effective substance (Ti) is 1%, and the amount of the catalyst added to the polyester synthesis is calculated as 5 ppm of the amount of polyester generated.

[0067] Polyester Synthesis:

[0068] Among them, the diol is taken as purified terephthalic acid, and the dibasic acid is taken as ethylene glycol. 333.3g of purified terephthalic acid, 160g of ethylene glycol and the finished catalyst dispersion are added into the reactor. After nitrogen is replaced 3 times, nitrogen is filled to 0.15MPa for esterification reaction. After the esterification water output reaches the theoretical value, the pre-condensation and final condensation reactions are started; wherein, the esterification temperature is 230-240°C, the esterification pressure is normal pressure-0.4MPa, and the esterification time is 2.5h; the pre-condensation temperature is 265°C, the vacuum degree is 100-150Pa, and the reaction time is 1.0h; the final condensation temperature is 272°C, the vacuum degree is 5-20Pa, and the reaction time is 1.0h, until the stirring power reaches the set value, and the material is cut into pellets to make slices.

[0069] Example 5

[0070] Synthesis and dispersion process of a new type of nanoparticle titanium catalyst:

[0071] The solvent is diethylene glycol, the conventional silicate chemical is tetraethyl orthosilicate, the epoxy silicate chemical is 3-glycidyloxypropyl triethoxysilane, the organic ligand compound is citric acid, and the titanium source is tetrabutyl tetratitanate. The preparation method comprises the following steps: (1) dissolving 12.5 g of tetraethyl orthosilicate and 11.14 g of 3-glycidyloxypropyl triethoxysilane in 118.18 g of diethylene glycol solvent, stirring to form a uniform and stable solution, to obtain solution A; and (2) adding 9.22 g of citric acid, an organic ligand compound, to solution A, so that the organic ligand reacts with the silanol with a functional group to achieve covalent bonding, to obtain solution B. The reaction temperature is 150°C and the reaction time is 2h; (3) 12.96g of 5% hydrochloric acid aqueous solution is gradually added to the above solution B, and the mixture is stirred continuously. Then the mixed solution is stirred evenly and placed at 50°C for 2h to hydrolyze the silicate chemicals to obtain a short-term stable silanol solution C; (4) Ammonia water is added to 19.44g of 10% solution C to catalyze the mutual condensation of semi-stable silanols to form nanoparticles to form a dispersion D; (5) The water and ammonia in the dispersion D are removed by heating. Then 61.77g of tetrabutyl titanate is added, and the organic ligands on the surface of the nanoparticles react with the titanium source to obtain a dispersion E, which is a mixture of the catalyst and alcohol by-products; (6) The dispersion E is centrifuged and washed 8 times with deionized water to obtain a white slurry pre-product F; (7) The pre-product F is dispersed in deionized water, stirred and dispersed for 1h, and then subjected to high-speed shear treatment for 0.5h using a high-speed disperser, and then ground by a sand mill for 3h to obtain a finished catalyst. The particle size of the catalyst particles is between 20-60 nm, the dispersion medium is water, the percentage of the effective substance (Ti) is 1%, and the amount of the catalyst added to the polyester synthesis is calculated as 5 ppm of the amount of polyester generated.

[0072] Polyester Synthesis:

[0073] Among them, the diol is taken as purified terephthalic acid, and the dibasic acid is taken as ethylene glycol. 333.3g of purified terephthalic acid, 160g of ethylene glycol and the finished catalyst dispersion are added into the reactor. After nitrogen is replaced 3 times, nitrogen is filled to 0.15MPa for esterification reaction. After the esterification water output reaches the theoretical value, the pre-condensation and final condensation reactions are started; wherein, the esterification temperature is 230-240°C, the esterification pressure is normal pressure-0.4MPa, and the esterification time is 2.5h; the pre-condensation temperature is 265°C, the vacuum degree is 100-150Pa, and the reaction time is 1.0h; the final condensation temperature is 272°C, the vacuum degree is 5-20Pa, and the reaction time is 1.0h, until the stirring power reaches the set value, and the material is cut into pellets to make slices.

[0074] Comparative Example 1

[0075] 333.3g of purified terephthalic acid, 160g of ethylene glycol and 0.13g of ethylene glycol antimony catalyst (170ppm) were added to the reactor, and nitrogen was replaced 3 times and then filled to 0.15MPa for esterification reaction. After the esterification water output reached the theoretical value, the pre-polycondensation and final polycondensation reactions were started; wherein, the esterification temperature was 230-240°C, the esterification pressure was normal pressure-0.4MPa, and the esterification time was 2.5h; the pre-polycondensation temperature was 265°C, the vacuum degree was 100-150Pa, and the reaction time was 1.0h; the final polycondensation temperature was 275°C, the vacuum degree was 5-20Pa, and the reaction time was 1.5h, until the stirring power reached the set value, and the material was cut into slices.

[0076] Comparative Example 2

[0077] 333.3g of purified terephthalic acid, 160g of ethylene glycol and 0.012g of tetraisopropyl titanate (5ppm) were added to the reactor, and the nitrogen was replaced 3 times and then filled to 0.15MPa for esterification reaction. After the esterification water output reached the theoretical value, the pre-polycondensation and final polycondensation reactions were started; wherein, the esterification temperature was 230-240°C, the esterification pressure was normal pressure-0.4MPa, and the esterification time was 2.5h; the pre-polycondensation temperature was 265°C, the vacuum degree was 100-150Pa, and the reaction time was 1.0h; the final polycondensation temperature was 272°C, the vacuum degree was 5-20Pa, and the reaction time was 1.0h, until the stirring power reached the set value, and the material was discharged and pelletized into slices.

[0078] The corresponding polyester product indicators of the above Examples 1 to 5 and Comparative Examples 1 to 2 were tested: intrinsic viscosity, crystallization temperature, L value and b value were tested according to GB / T 14189-2015. The test results are shown in the following table:

[0079] surface

[0080]

[0081] By comparing Comparative Examples 1 and 2, the melting and crystallization temperatures of titanium polyester and antimony polyester differ by nearly 23°C, which is a significant difference. By comparing Examples 1 to 5 and Comparative Example 2, it can be shown that the titanium polyester prepared by adding nanoparticle-type titanium catalyst in the present invention has a relatively higher crystallization temperature than the titanium polyester prepared by using conventional titanium catalyst.

[0082] The raw materials and equipment involved in the present invention, unless otherwise specified, are all commonly used raw materials and equipment; the preparation methods involved in the present invention, unless otherwise specified, are all conventional methods used in the art.

[0083] The nanoparticles prepared by this synthesis method have both the functions of catalyst and nucleating agent. The synthesis process is simple and feasible, and the addition process is convenient to operate. Its main components have the advantages of being non-toxic, green and environmentally friendly, and low in cost, which fully meets the current industry development needs and has a significant promoting effect on the promotion and application of titanium catalysts.

[0084] The above-mentioned implementation modes are only preferred implementation modes of the present application and cannot be used to limit the scope of protection of the present application. Any non-substantial changes and substitutions made by technicians in this field on the basis of the present application shall fall within the scope of protection required by the present application.

Claims

1. A novel method for preparing a nanoparticle titanium catalyst, characterized in that: The preparation method comprises S1, dissolving conventional silicate chemicals and epoxy-containing silicate chemicals in a solvent, stirring until a uniform and stable solution is formed, to obtain solution A, wherein the solvent is at least one of ethylene glycol and diethylene glycol; S2, adding an organic ligand compound to the solution A in step S1, so that the organic ligand in the organic ligand compound reacts with the silanol with a functional group in the solution A to achieve covalent bonding, thereby obtaining a solution B; S3, gradually adding hydrochloric acid aqueous solution to the above solution B, stirring continuously and heating, then stirring the mixed solution evenly and reacting it at 50-210° C. for 1-48 hours, so that the silicate chemicals are hydrolyzed to obtain a short-term stable silanol solution C; S4, adding ammonia water to the solution C in step S3 to catalyze the mutual condensation of semi-stable silanols to form nanoparticles, thereby forming a dispersion D; S5, the dispersion D in step S4 contains water, water and ammonia are removed by heating, and then a titanium source is added, and the organic ligands on the surface of the nanoparticles react with the titanium source to form a complex coordination reaction to obtain a dispersion E, which is a mixture of a catalyst and an alcohol by-product; S6, the dispersion E in step S5 is centrifuged and washed with deionized water to obtain a white slurry pre-product F; S7, dispersing the pre-product F in deionized water, stirring and dispersing for 0.1 to 3 hours, performing high-speed shearing treatment for 0.1 to 3 hours using a high-speed disperser, and then grinding for 0.5 to 5 hours using a sand mill to obtain a finished catalyst product.

2. The method for preparing a novel nanoparticle titanium catalyst according to claim 1, characterized in that: The molar ratio of the conventional silicate chemical to the epoxy-containing silicate chemical is 1-9:9-1, and the mass ratio of the total silicate chemical to the solvent A is 1-4:9-6.

3. A novel method for preparing a nanoparticle titanium catalyst according to claim 2, characterized in that: In the step S2, the molar ratio of the silanol with epoxy group to the organic ligand compound is 2-8:8-2.

4. A method for preparing a novel nanoparticle titanium catalyst according to any one of claims 1 to 3, characterized in that: The catalytic reaction temperature in step S4 is 30-200° C., the reaction time is 1-5 hours, and the particle size of the formed nanoparticles is 5-300 nanometers.

5. A novel method for preparing a nanoparticle-type titanium catalyst according to claim 4, characterized in that: The reaction temperature in step S5 is 100-200° C., the reaction time is 1-24 hours, the titanium source is at least one of tetraethyl titanate, tetrapropyl titanate, tetrabutyl titanate, tetraisopropyl titanate, tetra-tert-butyl titanate, and 2-ethyl-1-hexyl titanium; the molar ratio of the silanol with an epoxy group to the titanium source is 5-9:5-1.

6. A novel method for preparing a nanoparticle titanium catalyst according to claim 1, characterized in that: The catalyst particles in the finished catalyst product in step S7 have a particle size of 5 to 300 nm, the main component of the dispersion medium is deionized water, and the percentage of the effective substance Ti is 0.5% to 30%.

7. A novel method for preparing a nanoparticle titanium catalyst according to claim 6, characterized in that: The solid content of the finished catalyst in step S7 is 2-15%, and the titanium content is 0.5% to 5%.

8. Application of a novel nanoparticle titanium catalyst in polyester synthesis, characterized in that: The application method comprises A1. Add the finished catalyst as claimed in claims 1 to 7 and the dibasic acid to a diol solution at a temperature of 20 to 120° C., and stir rapidly until a uniform and stable mixed dispersion is formed. The amount of the finished catalyst added is calculated based on the amount of titanium element, and the content of the effective substance Ti in the added finished catalyst in the polyester is 1 to 100 ppm; A2, using diol and dibasic acid as raw materials to carry out esterification, pre-polycondensation and final polycondensation in sequence to prepare polyester in the form of chips, filaments or staple fibers, wherein the reaction temperature of the polyester is 220-280° C., the reaction pressure is 30 Pa-0.4 MPa, and the reaction time is 3.5-10.0 h; A3. Add the mixed dispersion before esterification or polycondensation during the polyester synthesis.

9. The use of a novel nanoparticle titanium catalyst in polyester synthesis according to claim 8, characterized in that: The polyester includes at least one of polyethylene terephthalate, polybutylene terephthalate and polybutylene adipate.

10. The use of a novel nanoparticle titanium catalyst in polyester synthesis according to claim 9, characterized in that: The dibasic acid includes at least one of purified terephthalic acid, isophthalic acid, naphthalene dicarboxylic acid, succinic acid, adipic acid, biphenyl dicarboxylic acid, and cyclohexane dicarboxylic acid; the diol includes at least one of ethylene glycol, 1,3-propylene glycol, 1,4-butanediol, 1,5-pentanediol, and 1,4-cyclohexanedimethanol; The molar ratio of the dibasic acid to the diol is 1:1.2-2.0.